Luc Tuymans - nice - Cohen, Joshua 1980-; Crary, Jonathan 1951-; Chassey, Éric de 1965-; Su, Wei 1982-; Tillman, Lynne 1947- (David Zwirner Books, 2024)
"This monograph of recent work reveals how Tuymans’s paintings grasp the mystery, strangeness, and possibilities of contemporary image making. It highlights a body of work that Tuymans has been working on since 2020, bringing together three exhibitions: Good Luck, at David Zwirner, Hong Kong; Eternity, at David Zwirner, Paris; and The Barn, at David Zwirner, New York. For this trilogy, Tuymans has heightened the contrast and saturation in his paintings, underscoring the urgency of our contemporary global moment. With texts by the novelist Joshua Cohen, the art historians Jonathan Crary and Éric de Chassey, the writer and critic Lynne Tillman, and the writer Su Wei, this publication offers an in-depth, dimensional understanding of both Tuymans’s outlook and his assertion of the relevance of painting in our digitally saturated world."--Gallery's website, accessed 10/04/2024